The Ulam Stability of Fractional Differential Equation with the Caputo-Fabrizio Derivative. (7th January 2022) - Wang, Shuyi
Abstract : The aim of this paper is to establish the Ulam stability of the Caputo-Fabrizio fractional differential equation with integral boundary condition. We also present the existence and uniqueness results of the solution for the Caputo-Fabrizio fractional differential equation by Krasnoselskii's fixed point theorem and Banach fixed point theorem. Some examples are provided to illustrate our theorems.